Strategi Pengembangan Unit Usaha BUMDes. (Studi Kasus: Program Kemitraan PT. Pertagas dengan BUMDes Sewu Barokah Desa Penatarsewu Kecamatan Tanggulangin Kabupaten Sidoarjo) - Mulyantari, Adhelya Dwi; Suharsono, Agus; Anwar, Anwar (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
Villages have the authority to improve public services for community members in order to accelerate the realization of general welfare, advance the economy of rural communities, and overcome national development gaps. The form of institution that meets these needs is the Village-Owned Public Agency or better known as BUMDes. In Sidoarjo Regency, there is one BUMDes that has quite good prospects, namely the Sewu Barokah BUMDes which is located in Penatarsewu Village, Tanggulangin District. The BUMDes has several units in it, including fisheries, agriculture, waste ksm, and restaurants which are the result of a partnership program between the private and regional governments, namely Resto Apung Seba. The Floating Resto is the result of a collaboration between BUMDes Sewu Barokah and PT. Pertamina Gas. However, currently there are several obstacles that are being experienced by the Floating Resto, namely the lower number of visitors. This is due to several factors, namely the covid-19 pandemic, then the location which is quite far from the crowds and the city center, less than optimal promotions, and incomplete facilities. After seeing the situation described above, it is necessary to find a solution, namely by choosing a more appropriate and effective strategy for BUMDes Sewu Barokah as the parent of the Floating Resto unit. Therefore, this study aims to analyze the internal and external factors of Resto Apung Seba in order to obtain a development strategy. This descriptive research uses a qualitative approach. Research data were collected through observation, in-depth interviews, and documentation. Head of BUMDes Sewu Barokah who is also the manager of Apung Seba Resto, restaurant manager, Community Development Officer (CDO) PT. Pertagas, as well as Resto's visitors as informants were determined by purposive sampling technique. The data analysis technique used SWOT analysis. The research findings show that the main strength of the Apung Seba Resto is that the restaurant has been known by the local community and outside the city because of its construction which is the result of collaboration with the private sector. The main drawback is that access to the location is quite difficult because it is far from the city center. The main opportunity that Resto has is raw materials that are easy to get because Penatarsewu Village is the center of the smoked fish industry. Then the main threat is that there has been no menu update since the restaurant was founded. The location of the Apung Seba Restaurant quadrant is in quadrant I, which is an advantage.